Transurethral resection of bladder cancer with or without fluorescence - Horňák, Jakub; Brisuda, Antonín; Babjuk, Marek (Current opinion in urology, 2023)
PURPOSE OF REVIEW: Transurethral resection of bladder cancer (TURBT) is in its standard form an inherently imperfect technique. Fluorescence-guided photodynamic diagnosis (PDD) represents one way to improve the outcome by enhancing tumour detection. Fluorescence has been used in connection with bladder cancer since the 1970s, with a number of studies being published since then. However, the method is still not recommended as a standard part of TURBT mainly because of the limited level of evidence of concerned studies, questionable cost-effectiveness and even contradictory results. The review lists the latest articles covering this topic. RECENT FINDINGS: Several recently published meta-analyses reviewed a series of randomized controlled trials (RCTs) concerning PDD assisted TURBT. Results were generally supporting the positive effect on reduction of recurrence rate. However, the mentioned meta-analyses are overlapping in terms of reviewed RCT that provide only a low level of evidence according to a recent Cochrane review. Supposed limitations of PDD (timing of the procedure, low specificity) and possible solutions are also covered. SUMMARY: Most of the published data confirmed reduced early recurrence rate after PDD assisted TURBT comparing to standard TURBT. Its impact on late recurrence rate, progression rate or cost-effectiveness has not been sufficiently demonstrated.
Keywords: fluorescence; Neoplasm Recurrence, Local; fotosenzibilizující látky; cystektomie; transuretrální resekce močového měchýře; lidé; Fluorescence; Transurethral Resection of Bladder; Cystectomy; Urinary Bladder Neoplasms; nádory močového měchýře; Photosensitizing Agents; lokální recidiva nádoru; Humans